Discussion, Recommendations and Conclusions - Jauhar, Junaimah; Abdul Ghani, Ahmad Bashawir; Islam, Rabiul (Springer, 2016)
This chapter discusses the findings from the survey and its implication towards the brain drain phenomenon. Coverage by the mass media often states that Malaysians are attracted to other neighbouring countries as a result of better salaries, living conditions, better lifestyles but are all these claims true? Brain drain has always been the main agenda for policy makers as the loss of skilled personnel equates to slowdown in economic growth. Although there has been quite a number of researches on the phenomenon conducted by earlier researchers, but very few have attempted to conduct it quantitatively.